The influence of tourism and hospitality attributes on nation-brand image, national identity and behaviour intentions - Handayani, Bintang (2016)
Tourism and Hospitality attributes play a crucial role in predicting Nation-Brand Image (NBI) formation, National Identity (NI), Behavioural Intention (BI) and consumer experiential consumption. However, study on the relation of Tourism and Hospitality attributes and NBI in the context of emerging nation is still limited. Thus, this thesis aims to empirically examine the tourists‘ post-visit experience in forming NBI and BI. This research employs a quantitative approach with a small amount of supporting data from qualitative technique (interviews). Thirty interviews were performed followed by a field survey. A survey of 384 international tourists at three destinations in Indonesia, namely Bali, Yogyakarta and Jakarta, was conducted to test the research hypotheses. The findings reveal that there are significant relationships between heritage, service and hospitality, and natural attractions with BI. The result also showed that service and hospitality and natural attractions are significantly related to NBI formation while heritage is a significant predictor for NI. As for the indirect relationship between tourism and hospitality attributes and NBI, the relationships of services and hospitality and natural attractions are partially mediated by cultural homogeneity. Similarly, NBI partially mediates the relationships of heritage, service and hospitality and natural attractions and BI. Overall, the research framework demonstrates its validity as a research model. The framework offers a working definition and a tool for conceptualising and establishing NBI. The theoretical implication of this research is that it extends the Keller‘s theory of brand image, by adding the place-marketing and place-branding domains, and nation marketing. In particular, this research also adds a new research context of Indonesia‘s tourism and hospitality attributes and NBI. It is recommended that future study in this area should utilise different study context and different types of respondents. In addition, other empirical technique such as the structural equation modelling (SEM) and a qualitative approach i.e. phenomenology or an ethnographic may be employed to add robustness and to enrich research findings.